2003
DOI: 10.3727/000000003108747190
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Isolation and Transplantation in the Pig

Abstract: Hepatocyte transplantation (HTX) has received great expectation for the treatment of a wide spectrum of liver diseases. Considering the severe shortage of human livers for hepatocyte isolation, porcine hepatocytes are an attractive alternative to normal human hepatocytes. To develop such therapy, establishment of an efficient hepatocyte isolation and transplantation model that enables accurate assessment of safety and efficacy of HTX is extremely important. Porcine hepatocytes were isolated from a surgically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…After closing the abdomen, intravenous administration of 0.5 g/kg of D-Gal (Sigma, Saint Louis, MI) was conducted via the jugular route 24 h prior to cell transplantation. Both of the tubes were flushed with 1000 U of heparin (Aventis, Tokyo, Japan) to prevent blood clotting, capped, and then subcutaneously embedded for the following transplantation experiment, as previously reported [20]. Recipient pigs were randomly divided in the following groups: G1, single intraportal injection of reverted 16-T3 cells (1 · 10 9 cells) (n = 5); G2, single intraportal injection of primary isolated pig hepatocytes (1 · 10 9 cells, which were compatible to 5% mass of the whole of the pig liver) as a positive control (n = 3); and G3, intraportal injection of Ringer's Lactate solution as a negative control (n = 5).…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…After closing the abdomen, intravenous administration of 0.5 g/kg of D-Gal (Sigma, Saint Louis, MI) was conducted via the jugular route 24 h prior to cell transplantation. Both of the tubes were flushed with 1000 U of heparin (Aventis, Tokyo, Japan) to prevent blood clotting, capped, and then subcutaneously embedded for the following transplantation experiment, as previously reported [20]. Recipient pigs were randomly divided in the following groups: G1, single intraportal injection of reverted 16-T3 cells (1 · 10 9 cells) (n = 5); G2, single intraportal injection of primary isolated pig hepatocytes (1 · 10 9 cells, which were compatible to 5% mass of the whole of the pig liver) as a positive control (n = 3); and G3, intraportal injection of Ringer's Lactate solution as a negative control (n = 5).…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Porcine hepatocytes were prepared from Landrace pigs (JA West of Okayama, Okayama, Japan), weighing 10 kg, by a four-step retrograde perfusion method using collagenase and dispase, as previously described [20]. The isolated hepatocytes with cell viability of >85% were used for transplant experiments.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Hepatocytes were isolated from Chinese experimental miniature pigs using a modified four-step collagenase perfusion method as described elsewhere [31]. Firstly, excised liver lobes were perfused at 37 8C with 300 ml and then at 39 8C with 500 ml of perfusion buffer solution (PBS) composed of 9 g/L NaCl, 0.42 g/L KCl, 2.1 g/L NaHCO 3 , 0.9 g/L glucose and 4.78 g/L Hepes (Sigma-Aldrich Inc., USA) containing 0.37 g/L of EDTA (Gibco, USA).…”
Section: Isolation Of Porcine Hepatocytesmentioning
confidence: 99%
“…The characteristics of these patients are described in Supplementary Table S1. Normal PHHC were isolated using a modified four-step retrograde perfusion technique as reported previously (Maruyama et al, 2003;Meng et al, 2010). Cell morphologies of PHHC and hepatoma cell lines used in this study are shown in Supplementary Figure S1.…”
Section: Cell Lines and Patient Samplesmentioning
confidence: 99%